Effect of metaclopramide on urinary bladder smooth muscle contraction-relaxation mechanism - Ercan, Zubeyde; Zorlu, Gokhan; Bulmus, Ozgur; Serhatlioglu, İhsan; Yasar, Abdullah; Kacar, Emine (My University, 2022)
Objectives: Metoclopramide, a dopamine receptor antagonist, a benzamide, is a commonly used antiemetic drug in many diseases with nausea and vomiting. The aim of this study is to examine the effects of metoclopramide, which is also used in urinary system infections, on the urinarybladder contraction-relaxation mechanism. Methods: In the study, bladder tissue strips obtained from adult female Wistar rats in diestrus were placed in an isolated organ bath containing Krebs solution. The effect of metoclopramide at concentrations of 10 µM and 20 µM on sections where spontaneous contractions were observed under 1.5 g of tension was investigated. Results: Metaclopramide caused a statistically significant increase in the area under the contraction curve (AUC) and peak to peak (p-p) parameters of spontaneous bladder contractions at concentrations of 10 and 20 ?M (p < 0.01). Conclusions: Metaclopramide has an activator effect on spontaneous bladder contractions. This effect should be taken into consideration in clinical use, especially when used in urinary systeminfections.
Keywords: Rat; Metoclopramide; urinary bladder; isometric contraction